Pathophysiological Processes Causing the Development of Obesity - Badriddinov Oyatillo Usmonjon o‘g‘li (Miasto Przyszłości, 2025)
Obesity is an increase in body adipose tissue and an endocrine and metabolic disorder that has become epidemic worldwide. Obesity is defined differently in adults and children. In adults, it is a body mass index (BMI) that exceeds 30 kg/m2. Obesity is an increase in body adipose tissue and an endocrine and metabolic disorder that develops when caloric intake exceeds energy expenditure. Obesity is an epidemic that has occurred worldwide in both adults and children. Single-gene (rare) and polygenic disorders and metabolic disorders are associated with obesity, as are gene–environment interactions. Adipokines and gastrointestinal hormones are altered with obesity and contribute to associated complications.